The fruRBA Operon Is Necessary for Group A Streptococcal Growth in Fructose and for Resistance to Neutrophil Killing during Growth in Whole Human Blood - Valdes, Kayla M. (Infect Immun, 2016)
Bacterial pathogens rely on the availability of nutrients for survival in the host environment. The phosphoenolpyruvate-phosphotransferase system (PTS) is a global regulatory network connecting sugar uptake with signal transduction. Since the fructose PTS has been shown to impact virulence in several streptococci, including the human pathogen Streptococcus pyogenes (the group A Streptococcus [GAS]), we characterized its role in carbon metabolism and pathogenesis in the M1T1 strain 5448. Growth in fructose as a sole carbon source resulted in 103 genes affected transcriptionally, where the fru locus (fruRBA) was the most induced. Reverse transcriptase PCR showed that fruRBA formed an operon which was repressed by FruR in the absence of fructose, in addition to being under carbon catabolic repression. Growth assays and carbon utilization profiles revealed that although the entire fru operon was required for growth in fructose, FruA was the main transporter for fructose and also was involved in the utilization of three additional PTS sugars: cellobiose, mannitol, and N-acetyl-d-galactosamine. The inactivation of sloR, a fruA homolog that also was upregulated in the presence of fructose, failed to reveal a role as a secondary fructose transporter. Whereas the ability of both ΔfruR and ΔfruB mutants to survive in the presence of whole human blood or neutrophils was impaired, the phenotype was not reproduced in murine whole blood, and those mutants were not attenuated in a mouse intraperitoneal infection. Since the ΔfruA mutant exhibited no phenotype in the human or mouse assays, we propose that FruR and FruB are important for GAS survival in a human-specific environment.